Yasmin the Night Owl Fairy - Meadows, Daisy (London Orchard Books, 2010)
Get ready for an exciting fairy adventure with the no. 1 bestselling series for girls aged 5 and up.
Include Illustrations
Keywords: Fairies -- Walker, Rachel (Fictitious character)